Interactions between native and invasive species: A systematic review of the red squirrel-gray squirrel paradigm - Wauters, Lucas A.; Lurz, Peter W. W.; Santicchia, Francesca; Romeo, Claudia; Ferrari, Nicola; Martinoli, Adriano; Gurnell, John (Frontiers in Ecology and Evolution, 2023)
The eastern grey squirrel (Sciurus carolinensis) has been labelled as one of the 100 worst invasive alien species by the IUCN. In Europe, the species has been introduced to Britain, Ireland and Italy, and its subsequent spread has resulted in wide-scale extinction of native Eurasian red squirrels (Sciurus vulgaris) from the areas colonised by the grey squirrel. This replacement of a native by an alien competitor is one of the best documented cases of the devastating effects of biological invasions on native fauna. To understand how this replacement occurs, we present a systematic review of the literature on competition and interactions between red and grey squirrels. We describe the patterns of red and grey squirrel distribution in those parts of Europe where grey squirrels occur and summarise the evidence on the different processes and mechanisms determining the outcome of competition between the native and alien species including the influence of predators and pathogens. Some of the drivers behind the demise of the red squirrel have been intensively studied and documented in the past 30 years, but recent field studies and mathematical models revealed that the mechanisms underlying the red-grey paradigm are more complex than previously thought and affected by landscape-level processes. Therefore, we consider habitat type and multi-species interactions, including host-parasite and predator-prey relationships, to determine the outcome of the interaction between the two species and to better address grey squirrel control efforts.